A Reinterpretation of the Baturetno Formation: Stratigraphic Study of the Baturetno Basin, Wonogiri, Central Java - Purna Sulastya Putra; Eko Yulianto (Indonesian Journal on Geoscience, 2015)
DOI:10.17014/ijog.2.3.125-137This paper focuses on the Quaternary Baturetno Formation. An earlier research concluded that the black clay of the Baturetno Formation formed as a ‘palaeolake’ deposit. The ‘palaeolake’ was interpreted to form due to the shifting course of the Bengawan Solo Purba River in relation to Pliocene tectonic tilting in the southern Java. The stratigraphy of the Baturetno Formation was observed in the western part of the Baturetno Basin, and based on marker beds, the Baturetno Formation was classified into three units: (1) Gravel unit (GR) in the upper part, (2) clay unit (CU) in the middle part, and (3) sand-gravel unit (SG) in the lower part. There are floating gravel fragments of andesite, claystone, coral, and limestone with diameters of up to 10 cm in the clay unit. The particle size of sediment reflects the environment, but the lake deposition occurs under very quiet conditions. The occurrence of these fragments within the clay cannot be explained if the clay was deposited within a lake environment. The occurrence of floating fragments in the black clay of Baturetno Formation can best be explained through mudflow process. The cohesive strength of the mudflow is responsible for the ability of large fragments to float within the mud matrix. In general, the Baturetno Formation is inferred to be an alluvial fan deposit. The presence of sand, gravel, and mud are characteristics of alluvial fan deposits.